An electronic companion to molecular cell biology a multimedia study aid - Van Buskirk, Robert Grenville (Cognito Learning Media, 1997)
Multimedia study guide on molecular cell biology featuring review and self-testing, including multiple choice, drag and drop, true/false, and fill-in-the-blank questions.